MODEL INOVASI PENGEMBANGAN KURIKULUM PAI UNTUK MENGHADAPI REVOLUSI INDUSTRI 4.0 - Alif Achadah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2020)
The current quality of education depends on graduates produced by educational institutions. And the low competitiveness of graduates from educational institutions is a problem that must be addressed immediately. The way to overcome these problems is by innovation or changes in the field of curriculum applied in educational institutions. Particularly for the PAI curriculum, innovations must also be made aimed at realizing graduates of high intelligence and morality. And to achieve graduates who are in accordance with the objectives of PAI education it is necessary to examine the models in developing the PAI curriculum. This study uses a qualitative method that collects data using observation, interviews, and documentation. It is known that the development of innovation in the curriculum needs to be done as an effort to improve the quality of education and the quality of graduates from schools in welcoming the 4.0 era.